Կրկին Ս. Յովհաննէս Օձնեցի Կաթողիկոսի «Կանոնագիրք Հայոց» ժողովածոյի ընդգրկման խնդրի մասին - Ալեքսան Յակոբեան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В исследованиях последних лет мы показали, что оригинальная версия сборника «Книги канонов» Св. Ованеса Одзнеци сохранилась в рукописях Матенадарана им. Маштоца (№ 659 и 657, группа рукописей с 35 каноническими материалами). In the latest researches we have shown that the original version of the “Book of Canons” preserved in manuscripts № 659 and 657 (group Ee, with 35 canonical groups) of Mashtots Matenadaran (manuscript library) is close to the canonical collection, compiled by St. Hovhannes Odznetsi.
Keywords: Literature